Flagellin maintains eosinophils in the intestine. (February 2022) - Lv, Xiaodan; Chang, Qing; Wang, Qin; Jin, Qiao-Ruo; Liu, Hua-Zhen; Yang, Shao-Bo; Yang, Ping-Chang; Yang, Gui
Abstract: Eosinophils (Eos) are the major effector cells in allergic response. The regulation of Eo is not fully understood yet. Flagellin (FGN) has immune regulatory functions. This study aims to elucidate the role of FGN in maintaining Eo at the static status in the intestinal tissues. A mouse food allergy (FA) model was developed. Eo mediator levels in the serum or culture supernatant or intestinal lavage fluids were assessed and used as an indicator of Eo activation. The results showed that less FGN amounts were detected in the FA mouse intestinal tissues, that were negatively correlated with the Eo activation. Mast cell-derived chymase bound FGN to induce FGN degradation. FGN formed complexes with FcγRI on Eos to prevent specific antigens from binding FcγRI, and thus, to prevent Eo activation. Administration of FGN efficiently alleviated experimental FA. In conclusion, FGN plays a critical role in maintaining Eos at static status in the intestine. Administration of FGN can alleviate experimental FA. FGN may be a novel drug candidate to be used in the treatment of Eo-related diseases.